No longer enemies, not yet friends an American soldier returns to Vietnam - Downs, Frederick (New York : W W Norton & Company, 1991)
A former lieutenant who fought in Vietnam describes his emotional journey to reconciliation with his former enemies while participating in a humanitarian aid program in Vietnam.
First trip to Vietnam : Second Trip : Third Trip : Dr. Bui Tung Visits America : Fifth Trip : Index
Includes index.
Keywords: Vietnam -- Description and travel. -- 1975; Vietnam -- Relations -- United States; United States -- Relations -- Vietnam